2023
DOI: 10.7150/jca.86735
|View full text |Cite
|
Sign up to set email alerts
|

TNFSF10, an autophagy related gene, was a prognostic and immune infiltration marker in skin cutaneous melanoma

Abstract: Autophagy exerts a pivotal effect on skin cutaneous melanoma (SKCM). This study was aimed to investigate the expression of autophagy related genes (ARGs) in SKCM as well as its clinical value. Differentially expressed (DE) ARGs were downloaded from the intersection of SKCM data in GEPIA2 database and ARGs in Human Autophagy Database (HADB) database, and were verified in SKCM datasets GSE46517 and GSE15605. DE ARGs were enriched by Metascape online tools. According to GEPIA2 database, tumor necrosis factor-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Tumour necrosis factor-related apoptosis-inducing ligand 10 (TNFSF10) is a death ligand cytokine that is mainly expressed by effector immune cells to kill malignantly transformed cells 32 . As an autophagy gene, TNFSF10 has the potential to predict the prognosis of melanoma patients and serve as a therapeutic marker for melanoma 33 . TNFSF10 is downregulated in HCC and may serve as a potential therapeutic target for HCC 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumour necrosis factor-related apoptosis-inducing ligand 10 (TNFSF10) is a death ligand cytokine that is mainly expressed by effector immune cells to kill malignantly transformed cells 32 . As an autophagy gene, TNFSF10 has the potential to predict the prognosis of melanoma patients and serve as a therapeutic marker for melanoma 33 . TNFSF10 is downregulated in HCC and may serve as a potential therapeutic target for HCC 34 .…”
Section: Discussionmentioning
confidence: 99%
“…As reported, TNFSF10 is a promising anticancer agent for treating solid tumors, which has the unique property of inducing apoptosis in tumor cells while sparing normal ones [ [56] , [57] , [58] ]. It has also been reported that TNFSF10 was able to induce autophagy in certain cancer cells, however, how TNFSF10 induces autophagy has not been clearly elucidated [ 59 ]. MAPK8 activation mediated by TRAF2 and RIPK1 might be crucial for TNFSF10-induced autophagy [ 60 ].…”
Section: Discussionmentioning
confidence: 99%